2011
DOI: 10.1007/s11693-011-9081-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-like interference effect in gene expression: glucose-lactose destructive interference

Abstract: In this note we illustrate on a few examples of cells and proteins behavior that microscopic biological systems can exhibit a complex probabilistic behavior which cannot be described by classical probabilistic dynamics. These examples support authors conjecture that behavior of microscopic biological systems can be described by quantum-like models, i.e., models inspired by quantummechanics. At the same time we do not couple quantum-like behavior with quantum physical processes in bio-systems. We present argume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Where the term "quantum feature"has more traction, so to speak, is in the area where quantum probability (in decision making) is employed. In that same area do we …nd the di¢ cult concept of 'context' (Khrennikov (2010)). Quantum features occur also in the use of Fisher information in economics and …nance.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Where the term "quantum feature"has more traction, so to speak, is in the area where quantum probability (in decision making) is employed. In that same area do we …nd the di¢ cult concept of 'context' (Khrennikov (2010)). Quantum features occur also in the use of Fisher information in economics and …nance.…”
Section: Introductionmentioning
confidence: 82%
“…Although we do not discuss such an interpretation in this paper (see for instance, Khrennikov, 2010;Haven, 2008), it needs to be indicated that if we were to formulate a 'preference for information'function then such device would be intimately related to the notion of probability as it is expressed in (14) above. This is quite di¤erent from the interpretation Ma (2010) gives to preferences for information, where such preferences can be unrelated to the probability measure assigned to an event.…”
Section: Example 22 Let (S) = R(s) Exp(il(s)); Where R(s) and L(s) Armentioning
confidence: 99%
See 1 more Smart Citation
“…2 In particular, in Basieva et al (2011) we demonstrated that one of the basic laws of classical probability theory, the law of total probability, is violated by well known experimental data, e.g., Inada et al (1996), on functioning of the lac-operon in E. coli bacteria. This violation can be interpreted as an interference effect which is similar to interference of probabilities in the two slit experiment with photons.…”
Section: Introductionmentioning
confidence: 92%
“…In this paper we use the quantum-like (QL) paradigm by which the formalism of QM can applied to describe measurements and information processes even outside of quantum physics, in particular, in biology (Khrennikov 2006;Accardi et al 2008). In a series of papers (Basieva et al 2011;Asano et al 2012a, b) we elaborated a QL model of a cell processing information in accordance with the laws of quantum information theory, cf. also Wanke et al (2009).…”
Section: Introductionmentioning
confidence: 99%